Relationship of the Role of Counselor, Knowledge, Trust, Values, and Social Relationship in Contraception Acceptors’ Decision of Using Intrauterine Device (IUD): Hubungan Faktor Peran Konselor, Pengetahuan, Kepercayaan, Nilai, dan Kekerabatan terhadap Keputusan Akseptor KB untuk Menggunakan Kontrasepsi Intrauterine Device (IUD) - Robby P. Sulbahri; Azhari Azhari; Firmansyah Basir; Theodorus Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: to assess the relationship of the role of counselor, knowledge, trust, values, and social relationship regarding acceptors’ decision in using intrauterine device at Dr. Mohammad Hoesin Hospital Palembang. Method: An observational analytical cross-sectional research carried out on June 2017 until September 2017 in the Department of Obstetrics and Gynecology Dr. Mohammad Hoesin General Hospital. 40 subjects were included. The frequency and distribution data were described in table form, bivariate analysis was performed to assess the relationship between independent and dependent variables statistically using Chi-square/Fisher Exact test. Multivariate analysis using logistic regression test was performed to assess which independent variable affects acceptors’ decision the most. Data analysis was performed using SPSS 18.0 version. Results: There were no statistically differences in age, duration of marriage, parity, number of children born alive, abortion, education, and jobs between the two groups (p<0.05). There was statistically significant relationship between knowledge, social relationship, and the role of counselor with contraception acceptors’ decision (p<0.005), but there was no significant relationship between trust and values with contraception acceptors’ decision (p>0.05). Meanwhile, the logistic regression analysis showed that the role of counselor significantly affects contraception acceptors’ decision (PR=108.989, p value=0.002). Concluson: The role of counselor is a factor that affects contraception acceptors’ decision in using IUD. Keywords: IUD, role of counselor, social relationship, trust, values, knowledge Abstrak Tujuan: untuk mengetahui hubungan faktor peran konselor, pengetahuan, kepercayaan, nilai, dan kekerabatan terhadap keputusan akseptor KB untuk menggunakan alat kontrasepsi IUD di Rumah Sakit Mohammad Hoesin Palembang. Metode: Penelitian analitik observasional rancangan cross sectional ini dilakukan di Departemen Obstetri dan Ginekologi Rumah Sakit Dr. Mohammad Hoesin/Fakultas Kedokteran Universitas Sriwijaya Palembang sejak bulan Juni sampai September 2017. Didapatkan sampel sebanyak 40 wanita melahirkan memenuhi kriteria inklusi. Frekuensi dan distribusi data dijelaskan dalam bentuk tabel, analisa bivariat untuk mengetahui ada tidaknya hubungan secara statistik antara variabel bebas dan dengan variabel terikat menggunakan uji Chi Square/Fisher Exact dan analisis multivariat untuk mengetahui variabel independen mana yang paling besar pengaruhnya terhadap keputusan akseptor KB untuk menggunakan alat kontrasepsi IUD menggunakan uji Regresi Logistik. Analisa data menggunakan SPSS versi 18.0. Hasil: Tidak terdapat perbedaan karakteristik pasien baik usia, lama pernikahan, paritas, jumlah anak hidup, abortus, pendidikan dan pekerjaan antara kedua kelompok (p<0,05). Terdapat hubungan yang signifikan antara pengetahuan, kekerabatan, dan peran konselor dengan keputusan akspetor KB IUD (p<0,05), namun tidak terdapat hubungan yang signifikan antara kepercayaan dan nilai dengan keputusan akspetor KB IUD (p > 0,05). Pada analisis regresi logistik didapatkan hasil peran konselor berpengaruh secara signifikan terhadap keputusan akseptor KB IUD (PR = 108,989, p value = 0,002). Keimpulan: Peran konselor merupakan faktor yang mempengaruhi keputusan akseptor KB untuk menggunakan alat kontrasepsi IUD. Kata Kunci: IUD, Peran Konselor, Kekerabatan, Kepercayaan Nilai, Pengetahuan.